Change of soils agrochemical properties at industrial plots polluted by fluorides - N. F. Pavlyukova; V. N. Kuchma (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Bìologìâ, Ekologìâ, 2006)
The changes of some agrochemical properties of soils of model plots closed to industrial enterprises with fluoride atmospheric emissions were studied. The alkalescence of soils at the plots was found. The reduction of content of the mobile forms of phosphorus, nitrite and nitrate forms of nitrogen and humus level in soil is caused by the increasing amount of nitrogen of ammonium compounds.